Diaspora Intercultural Communication of Malay students of Universiti Selangor (UNISEL) and Indonesian students of Bina Darma University on Student Mobility at Universiti Selangor (UNISEL) Malaysia - Putri Stevani A; Desy Misnawati (Dinasti Publisher, 2024)
Intercultural communication diaspora is a communication dynamic that occurs between individuals from different cultural backgrounds such as Bina Darma University students who take part in student exchange activities at Selangor University. This research was conducted to identify how students with different cultural backgrounds interact and communicate with each other and how they adjust and adapt to a new cultural environment. Bina Darma University students are faced with challenges in communicating and interacting, namely from differences in language, dialect and culture which make them quite difficult, but even so, there are strategies they use to face challenges in communicating and interacting so that conflicts or misunderstandings do not occur. Core intercultural communication aims to broaden students' insight into experiences, perceptions, challenges and strategies they use to face problems in adapting and adapting to a new cultural environment. By participating in this student exchange activity, you can help students improve intercultural communication with students from different cultural backgrounds and build good relationships with students from different cultures and change student stereotypes regarding intercultural communication and prejudices that arise when interacting or socializing with Malay students during student exchange activities so that they can communicate comfortably and confidently while maintaining their own cultural identity when communicating to minimize the existence of disputes or conflicts that arise due to cultural differences that both Malay students and Bina Darma University students have by using qualitative research methods in obtaining information as well as data related to research that has been researched.